The Reliability and Validity of the Australian Moral Disengagement Scale. Issue 3 (25th October 2016) - Newton, Nicola C.; Stapinski, Lexine A.; Champion, Katrina E.; Teesson, Maree; Bussey, Kay
Abstract : Background: The present study explored the reliability, validity, and factor structure of a modified version of the Moral Disengagement Scale (MDS), which comprehensively assesses proneness to disengage from different forms of conduct specific to Australian adolescents. Methods: A sample of 452 students ( M age = 12.79; SD = 1.93) completed the modified MDS and the Australian Self-Report Delinquency Scale. A multistep approach was used to evaluate the factor structure of the MDS. The sample was divided into exploratory ( n = 221) and cross-validation samples ( n = 231). Principal component analysis was conducted with the exploratory sample and multiple factor solutions compared to determine the optimal factor structure of the modified MDS. The final factor solution was confirmed in the cross-validation sample using confirmatory factor analysis. Internal consistency of the final scale and convergent validity with the delinquency questionnaire was also assessed. Results: Analyses resulted in a 22-item MDS for use in Australia, with four factors mapping onto the four conceptual categories of moral disengagement. The individual subscales demonstrated adequate to good internal consistency, and the total scale also demonstrated high internal consistency (α = 0.87). Convergent validity of the scale was established. Conclusions: The 22-item Australian MDS is a reliable and valid instrument for use within an Australian population.